Temperature-dependent structural plasticity of hippocampal synapses - Feng, Zhendong; Saha, Lopamudra; Dritsa, Clio; Wan, Qi; Glebov, Oleg O. (Frontiers in Cellular Neuroscience, 2022)
The function of the central nervous system (CNS) is strongly affected by temperature. However, the underlying processes remain poorly understood. Here, we show that hypothermia and hyperthermia trigger bidirectional re-organization of presynaptic architecture in hippocampal neurons, resulting in synaptic strengthening and weakening respectively. Furthermore, hypothermia remodels inhibitory postsynaptic scaffold into enlarged, sparse synapses enriched in GABAA receptors. This process does not require protein translation, and instead is regulated by actin dynamics. Induction of hypothermia in vivo enhances inhibitory synapses in the hippocampus, but not in the cortex. This is confirmed by the proteomic analysis of cortical synapses, which reveals few temperature-dependent changes in synaptic content. Our results reveal a region-specific form of environmental synaptic plasticity with a mechanism distinct from the classic temperature shock response, which may underlie functional response of CNS to temperature.